Implementation of Public Relations Management in Building the Image of Madrasah in Man 2 Pekanbaru - Suci Zami’ah Afwi Hasibuan; Oky Rahayu (Edumaspul: Jurnal Pendidikan, 2026)
Public relations management (PR) is one of the strategic functions in educational institutions that plays a role in building a positive image, establishing communication with the community, and strengthening relationships with various stakeholders. The existence of public relations is increasingly important in the digital era because educational institutions are required to be able to convey information quickly, accurately, and transparently to the public. This study aims to analyze the implementation of public relations management in building the image of madrasah in MAN 2 Pekanbaru. The research uses a qualitative approach with a case study method. Data was obtained through observation, interviews, and documentation. The research informants consist of the head of public relations and parties involved in the implementation of public relations activities. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of public relations management at MAN 2 Pekanbaru is carried out through internal and external communication, the use of publication media, marketing of educational services, the development of partnerships with stakeholders, and the implementation of electronic public relations (E-PR). The use of websites and social media is the main means of disseminating information to the public. In addition, cooperation with universities, government institutions, and the banking sector also supports the improvement of public image and trust in madrasas. The findings of the study show that effective public relations management contributes to strengthening the reputation and competitiveness of educational institutions.